STRATEGIC APPROACHES FOR REENGINEERING GUIDANCE AND COUNSELLING SERVICES IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE, NIGERIA - Egenti Uju Patricia (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study was carried out to identify strategic approaches for reengineering guidance and counselling services in public secondary schools in Anambra State, Nigeria. A descriptive survey research design was adopted in carrying out the study. The sample for the study was 255 respondents made up of guidance counsellors and secondary school managers in the area of the study. The instrument for data collection was a structured close-ended questionnaire titled: â€œStrategic Approaches for Reengineering Guidance and Counselling Services Questionnaire (SARGCSQ)â€. The instrument was validated by three experts while the reliability was ascertained using the Cronbach Alpha reliability method which yielded a coefficient of 0.88. Two hundred and fifty-five (255) copies of the questionnaire were administered to the respondents out of which 243 copies were completely filled and retrieved. Data collected were analysed using mean and standard deviation to answer the research questions and t-test statistics were used to test the null hypotheses at a 0.05 level of significance. The researcher in the study identified 10 capacity building approaches, 8 fund-related approaches and 10 programme review approaches for reengineering guidance and counselling services in public secondary schools in Anambra State. Findings indicated that there are no significant (p<0.05) differences in the mean ratings of the responses of guidance counsellors and school management on fund-related approaches and programme review approaches for reengineering guidance and counselling services in public secondary schools in Anambra State, Nigeria. Although, there was a significant (p<0.05) difference in the mean ratings of the responses of guidance counsellors and school management on capacity building approaches for reengineering guidance and counselling services in public secondary schools in Anambra State, Nigeria. Based on the findings, the study among others recommended that there should be constant capacity building of guidance counsellors through in-service training and retraining, relevant conferences, and workshops for improved efficiency in service delivery.